STUDI TENTANG EKSISTENSI DALIHAN NATOLU DALAM PESTA MANGADATI MASYARAKAT BATAK TOBA DI KECAMATAN TUALANG KABUPATEN SIAK - Christine Mesri; Hambali Hambali; Ahmad Eddison (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This research is motivated by community activities in the implementation of the traditional Mangadati tradition. The purpose of this study was to determine the existence of Dalihan Natolu in the Mangadati Party of the Toba Batak community in Tualang District. This study uses qualitative methods and data collection techniques that researchers do are observation, interviews and documentation. The Mangadati party is to make customs, implement, and preserve customs so that they always exist in the midst of society. Dalihan Natolu is the philosophy of life of the Toba Batak people in society which is taken from the function of the